2016
DOI: 10.1177/2325967116670117
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting Return to Play After Anterior Cruciate Ligament Injury in the National Football League

Abstract: Background:Anterior cruciate ligament (ACL) injuries are common in the National Football League (NFL). Limited literature exists regarding return to play (RTP) and the factors affecting RTP after ACL reconstruction in NFL players.Purpose/Hypothesis:To determine RTP rates after ACL reconstruction in NFL players and to ascertain which variables affect RTP in these players. We hypothesized that RTP in this population will be less than in the general population and similar to the limited studies published previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 16 publications
4
46
0
Order By: Relevance
“…Consistent with previous literature, those elite athletes who are in more established positions preoperatively (eg, higher draft round, more games played and started, etc) are more likely to RTP postoperatively 26. As well, as discussed in previous literature, position-specific advice is crucial to the management of athletic injuries and the RTP process 27.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with previous literature, those elite athletes who are in more established positions preoperatively (eg, higher draft round, more games played and started, etc) are more likely to RTP postoperatively 26. As well, as discussed in previous literature, position-specific advice is crucial to the management of athletic injuries and the RTP process 27.…”
Section: Discussionsupporting
confidence: 68%
“…Return to play has been evaluated in other cutting sports, including professional football. Eisenstein et al 7 and Shah et al 8 reported a 62% and 63% RTP rate, respectively, for National Football League athletes following ACL reconstruction. The RTP rate in professional football is notably less than the RTP rate found in studies evaluating NBA players.…”
Section: Figurementioning
confidence: 98%
“…involved in cutting sports is limited. [6][7][8] Fatigue in athletes has been shown to alter muscular activity and biomechanics. These alterations can lead to landing with a more straight leg, increasing an athlete's susceptibility to ACL tears.…”
mentioning
confidence: 99%
“… 15 , 24 Being selected earlier in the NFL draft (rounds 1-3) has been demonstrated to increase the likelihood of RTP after an ACL injury compared to being selected later in the NFL draft (rounds 4-7) or not being drafted. 15 , 24 Despite multiple studies demonstrating significant relationships between position type, draft round, and RTP rates, no study to date has examined the interplay between draft round and position type broadly across the NFL. In addition, whether players are able to return to preinjury levels of performance after RTP remains unknown, with information available only for running backs, wide receivers, quarterbacks, and kickers.…”
mentioning
confidence: 99%